A Case of Dorsal Spine Rhabdomyosarcoma in a 2 years old Child - Thapa, Shreejana; Gurung, Pritam; Shrestha, Janam; Acharya, Samir; Rajbhandhari, Pravesh; Pant, Basant (Annapurna Journal of Health Sciences, 2023)
Rhabdomyosarcoma is highly aggressive malignant form of mesenchymal tumor arising from skeletal muscle cells rhabdomyoblast, that have failed to fully differenciate. It is most commonly seen in the children before 12 year of age. Primary spinal rhabdomyosarcoma is very rare. A 2 year old girl presented with mass over right upper back and inability to move lower limb. Patient underwent dorsal laminectomy and excision of the mass. Histology and molecular pathology helps in definite diagnosis and further need of chemotherapy or radiotherapy.